Self-Reported Sleep Disturbance Mediates the Relationship Between PTSD and Cognitive Outcome in Blast-Exposed OEF/OIF Veterans. Issue 5 (September 2016) - Verfaellie, Mieke; Lee, Lewina O.; Lafleche, Ginette; Spiro, Avron
Abstract : Objectives: To examine the contribution of sleep disturbance to cognitive performance following blast exposure. Design: Correlational research evaluating self-reported sleep disturbance as a mediator of the association between the primary blast-related comorbidities of mild traumatic brain injury (mTBI) and posttraumatic stress disorder and cognitive outcome. Participants: One hundred sixty Operation Enduring Freedom/Operation Iraqi Freedom Veterans with a history of blast exposure assigned to 1 of 3 groups (no TBI, mTBI without loss of consciousness, and mTBI with loss of consciousness). Main Outcome Measures: Neuropsychological measures and self-report of sleep disturbance. Results: Increased posttraumatic stress disorder symptomatology was associated with worse performance in multiple cognitive domains. This association was mediated in part by self-reported sleep disturbance. Traumatic brain injury with loss of consciousness was associated with lower manual dexterity, but this association was not mediated by sleep disturbance. Conclusions: Our results highlight the importance of sleep disturbance as a factor contributing to cognitive outcome in individuals with posttraumatic stress disorder symptoms. They point to the importance of considering sleep problems in the diagnosis and treatment of cognitive deficits in veterans with blast exposure.